Forensic and Legal Victimology Education: The Actualization of Ethical Values in Law - Djunaedi (Institute of Medico-legal Publications Pvt Ltd, 2020)
Ethics need to be redeveloped as an effort to build the excellent forensic and legal victimology education, and law-abiding human beings with moral value. Being ethical means, therefore the awareness of the importance of ethics must always be a basic requirement in the forensic and legal victimology education order. The relation between ethics and educations is indeed close. There are many links which make both share similarities and differences, but the difference is not meant to separate them one from another. In addition, ethics and legal norms both have the same social aims, namely humans to do deeds according to the norms of society. Without a strong ethical principle, the awareness of forensic and legal victimology education may not grow well, the education may lose its substance. Even, the forensic and legal victimology is used as a tool to merely invigorate greed and selfishness. But by sticking to ethical principles, the awareness of forensic and legal victimology might grow well, as it may deliver and elevate human standards may realize social justice in Indonesia.